Aggregate Production with Consumption Externalities - Diamond, Peter A.; Mirrlees, James A. (Quarterly Journal of Economics, 1973)
I. Two consumers, 3. — II. Many consumers, 12. — III. Varying supply price, 20. — IV. Varying marginal utility of income, 22.